2022
DOI: 10.1038/s41529-022-00254-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of microbial communities on the corrosion behavior of steel in freshwater environment

Abstract: In a freshwater environment, accelerated corrosion of carbon and stainless steels is frequently observed. Here, an immersion study was conducted using nine types of steels in a freshwater pool for 22 mo. Accelerated corrosion was observed in carbon and Cr-containing steels and cast iron, whereas no visible corrosion was observed in stainless steels, even after 22 mo. Microbial community analysis showed that, in general corrosion, Fe(II)-oxidizing bacteria were enriched in the early corrosion phase, Fe(III)-red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…Higher Cr content in the S42000 steel and 15% Cr-stainless steel and Ni and Mo doping in the S41426 steel could have contributed to higher corrosion resistance compared with those of the S40300 stainless steel. Because our previous study showed corrosion in 9% Cr-steel immersed in freshwater ( Wakai et al, 2022 ), the Cr-content in the S42000 steel in the present study may be close to the threshold value for corrosion susceptibility in this environment. Although S40300 stainless steel generally does not corrode in freshwater environments, localized corrosion in check valve plugs made from S40300 stainless steel has been observed in actual facilities.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Higher Cr content in the S42000 steel and 15% Cr-stainless steel and Ni and Mo doping in the S41426 steel could have contributed to higher corrosion resistance compared with those of the S40300 stainless steel. Because our previous study showed corrosion in 9% Cr-steel immersed in freshwater ( Wakai et al, 2022 ), the Cr-content in the S42000 steel in the present study may be close to the threshold value for corrosion susceptibility in this environment. Although S40300 stainless steel generally does not corrode in freshwater environments, localized corrosion in check valve plugs made from S40300 stainless steel has been observed in actual facilities.…”
Section: Discussionsupporting
confidence: 72%
“…Amplicon sequencing was conducted to understand the differences in microbial communities in biofilms on metal surfaces over time. In 40 samples, 894,482 reads from S30400 and S31600 stainless steels (accession numbers: DRR334907–DRR334916; Wakai et al, 2022 ) and 2,774,371 reads, ranging from 40,565 to 128,474, from the rest were obtained. Thus, from a total of 3,668,853 reads, alpha and beta diversity and taxonomy plots were analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations